PENGEMBANGAN BAHAN AJAR IPA BERBASIS E-BOOK SEBAGAI MEDIA PEMBELAJARAN KELAS V SEKOLAH DASAR - Gilang Zenny Wibisari; Petra Kristi Mulyani (Program Studi PGSD Universitas Flores, 2023)
Based on the problems found in the learning process, it shows the limited variety of digital learning media that teachers have in delivering science material. The media used is limited to print media only. With simple media the teacher must explain the material repeatedly to students so that learning is not optimal and efficient. The research deSign used is research and development, a research method used to produce a product to be tested for feasibility and effectiveness. This research was conducted to develop products in the form of e-book-based science teaching materials as learning media for fifth grade elementary school students. The research deSign of the ADDIE development model goes through five stages, namely analysis, deSign, development, implementation and evaluation. Based on the results of the independent sample test, a positive hypothesis was obtained because there was a difference in the average student learning outcomes after using learning media in the form of e-book-based teaching materials on Heat and Transfer when compared to students who did not use media. There is a change in the average difference in student learning outcomes after using media in the form of e-book-based teaching materials. Based on the results of the research and discussion of media development, it can be interpreted that the developed e-book-based teaching material media is suitable for use in science learning on heat and transfer material in grade V SD, with appropriate criteria from media and material experts as well as teacher and student responses.